Morphological and physico-chemical properties of British aquatic habitats potentially exposed to pesticides. - Brown, Colin D.; Turner, Nigel; Hollis, John; Bellamy, Patricia H.; Biggs, Jeremy; Williams, Penny; Arnold, Dave; Pepper, Tim; Maund, Steve (Elsevier, 2006)
Approaches to describe the exposure of non-target aquatic organisms to agricultural pesticides can be limited by insufficient knowledge of the environmental conditions where the compounds are used. This study analysed information from national and regional datasets gathered in the UK describing the morphological and physico-chemical properties of rivers, streams, ponds and ditches. An aggregation approach was adopted, whereby the landscape was divided into 12 hydrogeological classes for agricultural areas and a 13th class that comprised non-agricultural land. The data describe major differences in the abundance, dimensions and chemistry of waterbodies in the different landscapes. There is almost an order of magnitude difference in the total input of pesticide per unit area between the different landscapes. Ditches are shown to be most proximate to arable land, streams and rivers intermediate and ponds the least proximate. Results of the study have implications for the development of standard scenarios for use in protective screening steps within the risk assessment. Data can be used to produce more realistic estimates of the exposure of aquatic systems to pesticides and to examine how that exposure varies across the landscape.
Keywords: Landscape; Waterbody; Risk assessment; Database